Determination of Segari Rock Slope Excavation Technique using Geological Strength Index (GSI) - Roslan, R; Omar, RC; Baharuddin, I.N.Z.; Taha, Hairin; Fared, M.M.; Hashim, W.N.S.W. (International Journal of Engineering and Technology, 2018)
Segari - Ayer Tawar rock materials were generally characterized as slightly weathered (Grade II) to moderately weathered (Grade III).Â  Laboratory tests such as Brazilian tensile strength and point load strength index including direct shear strength were carried out using collected weathering sample from borehole to assess the rock strength. Hence, index testing was used to predict geological strength index, rock failure criterion from Hoek-Brown and deformation modulus mainly for the classification of rock mass engineering properties.Â  The relationship between the uniaxial compressive strength and geological strength index of rocks were used in proposing suitable methods for cutting the rock slope.